Uncertainty of the Legal Regulation of Relations in the Sphere of Comparative Advertising: the Essence of the Problem and Possible Solutions - FROLOVA, Evgenia E.; BELIKOVA, Ksenia M.; BADAEVA, Natalia V.; ERMAKOVA, Irina V. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The article analyzes the norms on the prohibition of incorrect comparison in advertising, listed in Clause 1, Part 2 of Article 5 (Federal Law of Russian Federation ‘On Advertising’, hereinafter – the Law on Advertising) and Article 14.3 of Federal Law of the Russian Federation ‘On Protection of Competition’ (Federal Law of the Russian Federation ‘On Protection of Competition’, hereinafter – the Law on Protection of Competition), from the point of view of their application by the courts and FAS Russia when considering the relevant case category. The authors consider the rule on prohibition of incorrect comparison as a central rule regulating legal relations in the sphere of advertising, which contains a comparison of the advertised goods with competitors’ goods (comparative advertising). The problem is that none of the laws indicate which comparison is correct and which is incorrect. Such uncertainty exists in Russian legislation since 1991, after the adoption of the Federal Law of the RSFSR ‘On Competition and Restriction of Monopolistic Activity in Commodity Markets’ (Federal Law of the RSFSR ‘On Competition and Restriction of Monopolistic Activity in Commodity Markets’). This leads to the fact that entrepreneurs rarely use this advertisement, courts and FAS Russia, when considering the appropriate category of cases, are forced to subjectively assess the situation and draw a conclusion about the correctness or incorrectness of the comparison made in advertising. After analyzing the jurisprudence and practice of the FAS Russia, the authors managed to establish a number of criteria on which this or that comparison in advertising should be recognized as incorrect.